Separate Misspecified Regressions and the U.S. Long-Run Demand for Money Function - McAleer, Michael; Fisher, Gordon; Volker, Paul (The Review of Economics and Statistics, 1982)
Michael McAleer, Gordon Fisher, Paul Volker, Separate Misspecified Regressions and the U.S. Long-Run Demand for Money Function, The Review of Economics and Statistics, Vol. 64, No. 4 (Nov., 1982), pp. 572-583